EFFECT OF EDUCATION AND TRAINING LEVEL, COMPETENCY ON EMPLOYEE PLACEMENT AT ELITE HOTEL TEMBILAHAN - Widyawati; Shahrizal; Nelva Siskawati; Bayu Fajar Susanto (Jurnal Indragiri Penelitian Multidisiplin, 2022)
The purpose of this study is to determine the effect of the level of education and training, competence on employee placement at Hotel Elite Tembilahan. This research was conducted at Hotel Elite Tembilahan which is located at Jl. H. Arsyad Ahmad No. 2, Tembilahan City, Tembilahan, Indragiri Hilir Regency, Riau 29214, Indonesia. The population and sample in this study were employees of Hotel Elite Tembilahan, totaling 30 people. The sampling method used by the author is the Saturated Sampling Technique (census). Based on the research results, the regression equation Y = 5.439+0.868X1+0.790X2. Education and training variables affect the Placement of Elite Tembilahan Hotel Employees. Competency variable has an effect on employee placement at Elite Tembilahan Hotel. Based on the F-Test Test that the variables of education and training, competence jointly affect the placement of employees at Hotel Elite Tembilahan